2006
DOI: 10.1093/jac/dkl058
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of specific gene mutations associated with isoniazid or rifampicin resistance in Mycobacterium tuberculosis clinical isolates using non-fluorescent low-density DNA microarrays

Abstract: The LCD array protocol takes 45 min (15 min 'hands-on' time) after prior PCR amplification. Only minimal laboratory equipment is required. LCD arrays provide a rapid and economical method to characterize mutations in codon 315 of the katG gene, in the mabA-inhA regulatory region and in the rpoB gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 34 publications
0
25
0
3
Order By: Relevance
“…Aragon et al developed a fast low cost and low density DNA microarray (LCD array) for the detection of mutations that confer isoniazid or rifampicin resistance in MTB isolates. They observed that LCD was 100% concordant with the sequencing data for H resistance and 93.8% concordant for R resistance [42]. A sensitive and specific microarray was designed by Yao et al to detect mutations in the rifampin resistance determining region of rpoB and loci in katG and inhA associated with H resistance.…”
Section: Therapy and Susceptibility Testingmentioning
confidence: 99%
“…Aragon et al developed a fast low cost and low density DNA microarray (LCD array) for the detection of mutations that confer isoniazid or rifampicin resistance in MTB isolates. They observed that LCD was 100% concordant with the sequencing data for H resistance and 93.8% concordant for R resistance [42]. A sensitive and specific microarray was designed by Yao et al to detect mutations in the rifampin resistance determining region of rpoB and loci in katG and inhA associated with H resistance.…”
Section: Therapy and Susceptibility Testingmentioning
confidence: 99%
“…A low-cost and -density DNA microarray was designed to detect mutations that confer isoniazid and rifampin resistance in M. tuberculosis isolates. The low-cost and -density array protocol takes 45 min after PCR amplification, with only minimal laboratory equipment required (Aragon et al, 2006). Antonova and colleagues developed a method for the detection and identification of mutations in the M. tuberculosis genome determining resistance to fluoroquinolones by hybridization on biological microchips (Antonova et al, 2008).…”
Section: Gene Expression Profiles Of Drugs Resistance Inhibitors Anmentioning
confidence: 99%
“…For example, it has been used to distinguish different strains of Pseudomonas [6] or Mycobacterium tuberculosis [7]. The microarray has even been used to characterize mutations in the rpoB and katG genes that confer rifampin and isoniazid resistance in M. tuberculosis [8]. Microarrays are also being incorporated in some clinical laboratories for the rapid detection and classification of methicillin-resistant Staphylococcus aureus, determination of antimicrobial drug resistance in several pathogens such as Enterococcus and Mycobacterium tuberculosis, as well in diagnosis of sepsis [8][9][10].…”
Section: Bacteria Detectionmentioning
confidence: 99%
“…The microarray has even been used to characterize mutations in the rpoB and katG genes that confer rifampin and isoniazid resistance in M. tuberculosis [8]. Microarrays are also being incorporated in some clinical laboratories for the rapid detection and classification of methicillin-resistant Staphylococcus aureus, determination of antimicrobial drug resistance in several pathogens such as Enterococcus and Mycobacterium tuberculosis, as well in diagnosis of sepsis [8][9][10]. Besides detection and identification of pathogens, microarrays are a good option for characterizing genetic differences between isolates of the same species to the strain level.…”
Section: Bacteria Detectionmentioning
confidence: 99%